Research in cosmeceuticals and nutraceuticals, inventi - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Cosmeceuticals and Nutraceuticals are two fastest emerging areas fueling the healthcare market; surprisingly, pharmaceuticians are not venturing into this despite the fact that they can very easily result into enterprising innovations and climb the ladder to becoming rich through the path of entrepreneurship in this segment.